2020
DOI: 10.1016/j.cmi.2020.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the risk of hyperkalaemia and acute kidney injury with cotrimoxazole: a retrospective observational study

Abstract: Objectives: Increasing antimicrobial resistance has renewed interest in older, less used antimicrobials. Cotrimoxazole shows promise; however, hyperkalaemia and acute kidney injury (AKI) are potential complications. Identifying risk factors for and quantification of these events is required for safe use. This study aimed to evaluate predictors of cotrimoxazole-associated AKI and hyperkalaemia in a clinical setting. Methods: Patients prescribed cotrimoxazole were identified using electronic healthcare records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
2
17
2
Order By: Relevance
“…Our results indicated that 21.2% of the patients that received TMP/SMZ developed AKI, which is higher than the results from previous studies (19,20). Retrospective analysis of (20). However, both studies were based on adult populations, and AKI was diagnosed using the Kidney Disease Improving Global Outcomes classification system, which tests for an increase in serum creatinine and serum urea.…”
Section: Discussioncontrasting
confidence: 55%
“…Our results indicated that 21.2% of the patients that received TMP/SMZ developed AKI, which is higher than the results from previous studies (19,20). Retrospective analysis of (20). However, both studies were based on adult populations, and AKI was diagnosed using the Kidney Disease Improving Global Outcomes classification system, which tests for an increase in serum creatinine and serum urea.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous reports indicated hypertension, diabetes, low baseline eGFR, cardiac disorders, high-dose SMX/TMP, concomitant use of renin-angiotensin system blockers, potassium-sparing diuretics, and potassium supplements are risk factors for AKI associated with SMX/TMP [ 8 , 9 , 12 , 13 ]. However, our study examined whether loop diuretics could increase the risk of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AKI is a known prognostic factor regardless of the underlying disease [ 11 ]. Previous reports have identified various risk factors for developing AKI associated with SMX/TMP, such as the presence of hypertension, diabetes, low baseline estimated glomerular filtration rate (eGFR), cardiac disorders, administration of high-dose SMX/TMP, and concomitant use of renin-angiotensin system blockers, potassium-sparing diuretics, and potassium supplements [ 8 , 9 , 12 , 13 ]. However, it remains controversial about risk factors and no study has investigated the influence of loop diuretics on AKI associated with SMX/TMP.…”
Section: Introductionmentioning
confidence: 99%
“…Although the frequency of AEs does not seem to have been related to the eGFR at the start of TMP-SMX, we observed that the discontinuation rate for AEs was higher when the eGFR was <30 ml/min/1.73 m² (notably discontinuation because of increased SCr). In our study, no dose adjustment was made in patients with eGFR <30 ml/min/1.73 m² even though several studies 7,24,25 strongly support this approach. This factor may also partly explain the high rate of discontinuation for increased SCr in our patients.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 76%
“…Regarding safety, a retrospective study including 214 patients receiving short-course (median duration, 7 days) TMP-SMX, mostly for respiratory or skin and soft tissue infections, identified that 42 patients (19.6%) met acute kidney injury criteria and 33 (15.4%) experienced hyperkalemia. 7 However, SOT recipients with nocardiosis receive TMP-SMX at higher dose (10-20 mg of TMP/ kg/d) and longer duration (~6 months). Data in this specific context are therefore required.…”
Section: Introductionmentioning
confidence: 99%